2020
DOI: 10.3390/md18050249
|View full text |Cite
|
Sign up to set email alerts
|

Carrageenan-Based Acyclovir Mucoadhesive Vaginal Tablets for Prevention of Genital Herpes

Abstract: Women are the most affected by genital herpes, which is one of the most common sexually transmitted infections, affecting more than 400 million people worldwide. The application of vaginal microbicides could provide a safe method of protection. Acyclovir is a safe and effective medication for vaginal administration, and numerous benefits have been observed in the treatment of primary or recurrent lesions due to genital herpes. Vaginal tablets based on a combination of the polymers iota-carrageenan and hydroxyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 72 publications
1
29
0
Order By: Relevance
“…Hence, the biomedical importance of CG as bioactive components that make it possible to improve pharmaceutical formulations and in certain cases be adjuncts to other active principles. The biological and chemical properties of CG are the main reasons they are used in drug delivery systems [ 40 , 106 ].…”
Section: Carrageenan In Biomedical Applicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, the biomedical importance of CG as bioactive components that make it possible to improve pharmaceutical formulations and in certain cases be adjuncts to other active principles. The biological and chemical properties of CG are the main reasons they are used in drug delivery systems [ 40 , 106 ].…”
Section: Carrageenan In Biomedical Applicationsmentioning
confidence: 99%
“…The major applications in the field of biomedicine are shown as a schematic layout in Figure 6 . CGs are applied in various pharmaceutical formulations, including tablets [ 106 , 108 ], suppositories [ 109 , 110 ], films [ 111 ], fast-dissolving inserts (FDIs) [ 63 ], beads [ 112 , 113 ], pellets [ 114 , 115 , 116 ], microparticles [ 117 , 118 , 119 ], nanoparticles [ 120 , 121 , 122 , 123 , 124 , 125 ], inhalable systems, injectables [ 126 ], and hydrogels [ 127 , 128 , 129 ]. In addition, recent studies have shown that CGs are promising candidates in tissue engineering, thanks to their similarity to native glycosaminoglycans [ 127 , 128 , 130 , 131 ].…”
Section: Carrageenan In Biomedical Applicationsmentioning
confidence: 99%
See 3 more Smart Citations